Myocardial injury mimicking acute myocardial infarction due to coronavirus infection in adults with pre-existing apical hypertrophic cardiomyopathy - Radityo Bagus Wicaksono; Mochamad Yusuf Alsagaff; Ricardo Adrian Nugraha (Journal of the Pakistan Medical Association, 2024)
Symptoms of apical hypertrophic cardiomyopathy (ApHCM) can mimic acute myocardial infarction (AMI). Following COVID-19 infection, the elevation of troponin in ApHCM might be confusing, due to its similarity with AMI. We report the case of a 64-year-old male patient presenting with exertional dyspnoea and chest discomfort. He had no history of coronary artery disease (CAD), but his swab test was positive for COVID-19. The physical examination was normal. The 12-lead electrocardiogram showed a sinus rhythm of 78 bpm, with deep inverted T waves in leads V2 to V6, I, and aVL, and left ventricular hypertrophy. An Echocardiographic examination showed an 18 mm apical wall thickness of the left ventricle. Laboratory tests revealed elevated hs- Troponin level, but diagnostic coronary angiography was normal. The diagnostic criteria fulfilled apical cardiac hypertrophic cardiomyopathy. Coronavirus can induce atypical cardiovascular symptoms in pre-existing ApHCM. Misdiagnosis and failure to recognize may result in inappropriate therapy and delay in definitive treatment. Keywords: Troponin, COVID-19, Echocardiography, Electrocardiography, Hypertrophy, Angiography, Dyspnea, Infarction